CD117: A novel ancillary marker for papillary thyroid carcinoma in fine‐needle aspiration biopsies. Issue 8 (11th June 2014) - Pusztaszeri, Marc P.; Sadow, Peter M.; Faquin, William C.
<x xml:space="preserve">Abstract</x> BACKGROUND c‐KIT/CD117 down‐regulation has been described in papillary thyroid carcinoma (PTC). In this study, the authors investigated CD117 as an ancillary immunocytochemical test for PTC in fine‐needle aspiration biopsy (FNAB). METHODS The expression of CD117 was assessed in cytologic samples of histologically confirmed classic PTC (n = 35) and in a control group of benign thyroid nodules (BTNs) (n = 30) using immunocytochemistry. The corresponding PTCs and BTNs from surgical resection specimens also were evaluated immunohistochemically for CD117. The expression of CD117 was assessed semiquantitatively using a scoring system from 0 to 5 that combined the proportion and the intensity of staining. RESULTS The difference in immunoreactivity for CD117 between PTC and BTNs was highly significant both in FNAB samples and in the corresponding histology samples (P < .0001). On cytology, most PTCs (74%; n = 26) lacked immunoreactivity for CD117, and 9 samples (26%) had faint reactivity in <2% of tumor cells (score, 0). In contrast, all BTNs (100%; n = 30) were positive for CD117, and at least 50% of the cells (score, 2‐4) were positive in 79% (n = 24) of BTNs. Results with corresponding histology were similar to the cytology results; most PTCs (89%; n = 31) lacked immunoreactivity for CD117, and 4 samples (11%) had faint reactivity in <2% of tumor cells. In contrast, all BTNs (n = 30) were variably positive for CD117 (score, 2‐4). Normal follicular epithelium also was positive for CD117 (score, 2‐4). CONCLUSIONS CD117 is expressed in both normal follicular epithelium and in BTNs. In contrast, expression of CD117 is absent or weak in PTC. These results suggest that CD117 may be useful as an ancillary marker for PTC. Cancer (Cancer Cytopathol) 2014;122:596–603 © 2014 American Cancer Society.